1046 DIAGNOSTIC PERFORMANCE OF CALCIUM SCORE ASSESSMENT IN ATRIOVENTRICULAR CONDUCTION DETERIORATION AFTER TAVI: A SINGLE CENTRE PILOT STUDY. (15th December 2022) - Di Costanzo, Assunta; Curcio, Antonio; Spaccarotella, Carmen; Mongiardo, Annalisa; Romano, Letizia Maria; Cardia, Giada; Panarello, Alessandra; Bruno, Federica; Spinali, Martina; Sportelli, Martina; Indolfi, Ciro
Abstract: Background: The risk of cardiac conduction system defects (CCD) after transcatheter aortic valve implantation (TAVI) remains high and requiring permanent pacemaker implantation (PPI) in 20% of the patients. Numerous studies have suggested that up to half of patients who underwent PPI within 30 days after TAVI do not depend on their PM at one year. The micro-calcific deposits of the atrioventricular node cannot be detected by standard echocardiography, while CT scan can reliably identify them. While pacemaker implantation was recommended according to clinical status and current guideline, in this small retrospective analysis, pre-procedural CT scan calcium quantification was considered an anatomical predictor of AV conduction prolongation until advanced disorder and cardiac block. We assume that differential calcium localization into the AV node might contribute to progression of conduction disorders until complete heart block. Aims: The objective of this pilot study is to evaluate the impact of calcium score assessment as a predictor of the development of CCD after TAVI. The goal is to evaluate the interaction between PM dependency and the value of calcium score at the CT scan pre-TAVI. the data collected in this single-center cohort analysis AIMS TO help identify patients at higher risk of permanent pacemaker implantation after TAVI pacemaker insertion and pacemaker-dependent patients at one year through CT calcium scoring. Methods: From January 2020 to September 2021, we retrospectively collected data from our institute. One-hundred and thirty patients without prior PM underwent TAVI in our institution. Overall mean age was 79, 7 years old with 57, 1% of females, with a pre-procedural diagnosis of aortic stenosis and a mean gradient of 47, 4 mmHg. At 30 days, PPI was reported in 21 patients (16, 1%). Out of twenty-one patients 47, 6% developed complete atrioventricular block, 19% developed atrioventricular block II grade type 2 and 33, 3% other conduction defects. The dependency at the implantation was 51, 1%. With a dedicated software at the CT scan, we assessed the calcium score located in three regions near the atrioventricular node: aortic valve, left ventricular outflow tract (LVOT) and anterior mitral annular (Figure 1). Two patients were excluded for the diagnosis of severe aortic stenosis low-flow low-gradient. The Primary endpoint was to identify patients who had higher risk of PPI after TAVI pacemaker insertion. Results: At 12 months follow-up, 23, 8% of patients died (n=5). All the remaining patients, 28, 5% had a high rate of ventricular pacing (Vp) at implantation (n=6). One year later at the follow up, three of these patients restored intrinsic rhythm and had a low Vp rate. The rate of patients found pacemaker-dependent at one year of follow-up was 76, 2%. Conclusions: Among 21 patients who requiring PPI after TAVI, at 12 months 14, 2% restored intrinsic rhythm. The methodology of calcium scoring outside the coronary arteries is still an active area of study. In the coming months, the collected data will be analyzed to assess the association between PM dependence at follow-up and calcium score on CT scan before TAVI.